Research progress of moxibustion for postoperative urinary retention in patients with hip fracture (艾灸在髋部骨折术后尿潴留中的研究进展) - ZHANG Pin (张聘); LIU Jie (刘洁); LI Jiao (李姣); DONG Yuxia (董玉霞); E Haiyan (鄂海燕); TANG Ling (唐玲) (Association of Integrative Nursing, 2023)
Postoperative urinary retention is one of the common complications after hip fracture surgery. This paper sorts out and analyzes the influencing factors of postoperative urinary retention of hip fracture and application effect of moxibustion in nursing of postoperative urinary retention, in order to provide more reference for improvement of early rehabilitation of patients after hip fracture surgery. (尿潴留是髋部骨折术后常见的并发症之一, 严重影响患者术后康复。本文整理和分析髋部骨折术后尿潴留的影响因素, 总结艾灸改善髋部骨折术后尿潴留临床应用现状, 旨在为更好地促进髋部骨折术后尿潴留患者的康复提供参考。)